Pengaruh Metode Latihan Sirkuit dan Drill Pass terhadap Ketepatan Passing Spin Atlet Rugby Jawa Barat - Agustiawan, Dini; Saputra, Yudha Munajat; Dinangsit, Dinar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the effect of circuit pass and drill pass training methods on increasing the accuracy of rugby athletes' spin passes. The method used in this research is experimental. This method was chosen because the main aim of this research is to determine the impact of a treatment. This research uses a pretest-posttest group design research design, which involves one group, and a pretest is carried out, then a treatment is given for 16 meetings, and then a posttest (final test) is carried out with a schedule of January-February 2024. This research uses a saturated sampling technique because the population is relatively small. So the sample used in this research was 30 people. The instrument used is the rugby spin passing test. The results of the research show that the sig value (0.000) < 0.05, and it can be concluded that the pass circuit training method has an effect on increasing the accuracy of rugby athletes' spin passes. Meanwhile, the drill pass training method has a value of (0.000) < 0.05, meaning it has an influence on increasing the accuracy of rugby athletes' spin passes. Furthermore, the hypothesis test for the circuit pass and drill pass training methods has a value of (0.506) > 0.05, so it can be concluded that the two training methods do not have a significant difference in increasing the accuracy of rugby athletes' passing passes. Keywords: drill pass, pass circuit, rugby, spin pass